Research note: Complex evaluation of whole oats and dehulled oats as feedstuffs for broiler chickens - Nikoletta Such; Mohamed Ali Rawash; Valéria Farkas; Judit Poór; Kesete Goitom Tewelde; László Pál; Gábor Csitári; László Wágner; Eszter Péterné Farkas; Károly Dublecz (Poultry Science)
This study aimed to gain a better understanding of how the structural and viscous fibers of oats can affect the performance, some selected blood interleukins, short chain fatty acid content and microbiota composition of the ceca of broiler chickens. A floor pen trial was carried out with 576 Ross 308 broiler cockerels. Aside from a corn–soybean-based control diet (C), the two other treatments contained either 10, 10 and 20 % whole oats (WO) or dehulled oats (DO) in the starter, grower and finisher phases respectively. The diets were isocaloric and isonitrogenous, differing only in their structural and soluble fiber and fat content. DO diets resulted in significantly higher weight gain compared with the two other treatments. The best feed conversion ratio (FCR) was also measured in the DO treatment group. The higher fiber content of WO diets did not compromise the production traits in comparison with the control diet. DO treatment resulted in increased interleukin-1beta (IL-1β), whereas WO decreased interleukin-8 (IL-8) concentration of the blood serum at day 39. Both oat treatments reduced the abundance of lactic acid-producing genera, the acetate, butyrate and the total short chain fatty acid (SCFA) content in the ceca.